2010
DOI: 10.1371/journal.pone.0012845
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the mTOR Pathway Mediates Impairment of Synaptic Plasticity in a Mouse Model of Alzheimer's Disease

Abstract: BackgroundThe mammalian target of rapamycin (mTOR) is an evolutionarily conserved Ser/Thr protein kinase that plays a pivotal role in multiple fundamental biological processes, including synaptic plasticity. We explored the relationship between the mTOR pathway and β-amyloid (Aβ)-induced synaptic dysfunction, which is considered to be critical in the pathogenesis of Alzheimer's disease (AD).Methodology/Principal FindingsWe provide evidence that inhibition of mTOR signaling correlates with impairment in synapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
199
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(213 citation statements)
references
References 48 publications
12
199
1
1
Order By: Relevance
“…Indeed, inhibition of GSK3b, a downstream target of PI 3-kinase, prevents inhibition of hippocampal LTP by Ab [74]. Furthermore, GSK3 inhibitors are also reported to rescue LTP in a murine model of AD [78]. Thus, it is feasible that activation of PI 3-kinase and subsequent inhibition of GSK3b play a key role in leptin-dependent reversal of Ab inhibition of LTP.…”
Section: Leptin and Synaptic Function In Alzheimer's Diseasementioning
confidence: 99%
“…Indeed, inhibition of GSK3b, a downstream target of PI 3-kinase, prevents inhibition of hippocampal LTP by Ab [74]. Furthermore, GSK3 inhibitors are also reported to rescue LTP in a murine model of AD [78]. Thus, it is feasible that activation of PI 3-kinase and subsequent inhibition of GSK3b play a key role in leptin-dependent reversal of Ab inhibition of LTP.…”
Section: Leptin and Synaptic Function In Alzheimer's Diseasementioning
confidence: 99%
“…Studies using analogues for the gut hormone glucagon-like peptide-1 (GLP-1) such as liraglutide, which facilitate insulin release, have shown that even short-term treatment can improve learning and memory, in addition to improving glucose homeostasis in mice with diet-induced obesity [7]. Moreover, an increase of GLP-1 signalling in the brain has also been suggested as a promising strategy to ameliorate the degenerative processes observed in Alzheimer's disease [8], while studies crossing APP mice to mouse models with alterations in brain insulin-signalling have revealed an important role for insulin signalling and glucose homeostasis in cognitive behaviour in these mice [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These authors identified quinostatin as a novel mTOR inhibitor through a high-throughput and cell-based assay [47]. The mTOR signalling pathway is relevant to various human diseases, including AD [48]. In vitro studies showed that Ab was an activator of the PI3K/AKT pathway, which in turn activated mTOR [49].…”
Section: Biological Insights Into Small Moleculementioning
confidence: 99%